2021
DOI: 10.3390/foods10071668
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Nitrofurazone Metabolites in Animal-Derived Foods Based on a Background Fluorescence Quenching Immunochromatographic Assay

Abstract: Due to their facile synthesis and friendly functionalization, gold nanoparticles (AuNPs) have been applied in all kinds of biosensors. More importantly, these biosensors, with the combination of AuNPs and immunoassay, are expected to be used for the detection of different compounds with low concentrations in complex samples. In this study, a AuNPs-labeled antibody immunoprobe was prepared and combined with a fluorescence-quenching principle and a background fluorescence-quenching immunochromatographic assay (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The background fluorescence-quenching immunochromatographic assay (bFQICA) showed potential application for the quantitative determination of SEM in animal-derived foods. 51 Since the detection mode of this assay was a competitive reaction, environmental interference easily disturbed detection results. Zhang et al reported a freeze-synthesized bio-barcode immunoprotein-based multiplex fluorescence immunosensor to simultaneously determine four nitrofuran metabolites with a tedious preparation process.…”
Section: Resultsmentioning
confidence: 99%
“…The background fluorescence-quenching immunochromatographic assay (bFQICA) showed potential application for the quantitative determination of SEM in animal-derived foods. 51 Since the detection mode of this assay was a competitive reaction, environmental interference easily disturbed detection results. Zhang et al reported a freeze-synthesized bio-barcode immunoprotein-based multiplex fluorescence immunosensor to simultaneously determine four nitrofuran metabolites with a tedious preparation process.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, immunoassay was proposed in this study because of the advantages of rapidness, high-throughput, sensitivity, low-cost, simple pretreatment requirement. It is easy-to-use and has been widely applied in fields of food analysis [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, AuNPs-LFIA is known to have limited sensitivity because of AuNPs’ narrow particle size range and poor colloid stability. Wu et al [ 6 ] described a background fluorescence-quenching immunochromatographic assay (bFQICA) in which AuNPs were used to quench the fluorescence of a background fluorescence baseboard instead of using the colorimetric method. Such a method was optimized, validated, and applied in the rapid on-site detection of nitrofurazone metabolite of semicarbazide (SEM) residues in animal-derived foods (egg, chicken, fish, and shrimp).…”
mentioning
confidence: 99%